The World Bank Annual Report 2002 : Volume 1. Main report - World Bank (Washington, DC, 2013)
This annual report covers the period from July 1, 2001, to June 30, 2002, and is prepared by the Executive Directors of both the International Bank for Reconstruction and Development (IBRD) and the International Development Association (IDA). The first of two volumes discusses the World Bank's goals and strategies; overviews Bank activities in fiscal year 2002; examines progress on the Millennium Development Goals and project and loan performance; addresses the social, institutional, and economic dimensions of poverty; presents regional analyses of Bank operations; and provides organizational information. The second volume comprises the complete Management's Discussion and Analysis, audited financial statments of the IBRD and IDA, and appendixes.